The effects of life review-based collage book making on psychosocial functioning and discrepancy between patients' and hospital staff's perception of daily functioning in long-term hospitalized patients with schizophrenia: A randomized controlled trial. - Kaneko, Fumiko; Ueno, Kazumi; Hirasawa, Rei; Saita, Kazuya; Okamura, Hitoshi (Archives of Psychiatric Nursing, 2024)
The purpose of this study was to investigate the psychosocial effects of life review-based collage book making on long-term inpatients with schizophrenia, and to verify the effectiveness of this program in reducing the discrepancy between self-perception and others' evaluation of patients' day-to-day functioning. Participants were randomly assigned to intervention or control group. The intervention group participated in an individual program of life review-based collage book making. At three evaluation points (pre-and post-intervention and at 3-month follow-up) the patients rated their subjective difficulties, and the staff rated the objective severity of the patient's day-to-day functioning, using the Schizophrenia Cognition Rating Scale Japanese version (SCoRS-J). The Profile of Mood Status-Brief Form (POMS), Recovery Assessment Scale, and Life Skills Profile were used to assess psychosocial functioning, and the changes in scores on the scales were compared between the two groups. In addition, for those with large discrepancy between patient and staff rating scores on the SCoRS-J at baseline, the change in the discrepancy scores were compared between the two groups. As a result, there was a significant group main effect and interaction between the two groups in the changes in the Confusion subscale scores of the POMS, indicating an alleviation of confusion in this program. In addition, for those with large discrepancy scores on the SCoRS-J, there was a significant group main effect and interaction between the two groups in discrepancy scores, indicating that this program can contribute to the reduction of discrepancies in the perceptions, and to the collaborative approach to treatment. • We examined life review-based collage book making among patients with schizophrenia. • Participants were randomly assigned to intervention (book making) or control group. • The program reduced patients' confusion, which persisted for three months. • The program reduced perceptual discrepancies between patients and healthcare staff. • The program may facilitate a collaborative approach to treatment.